PERBUATAN MANUSIA MENURUT MUTAKALLIMĪN DAN PENGARUHNYA TERHADAP INTERPRETASI KONSEP QADR - Irsyad Amrullah (UIN Raden Mas Said Surakarta, 2022)
This study reviews the ideas of the Kalām scholars regarding human actions and their influence on the interpretation of the concept of Qadr, with the aim of describing the good and bad of human actions, the consequences of interpreting good and bad actions, the correlation of the concept of al-Taḥsīn wa al-Taqbīḥwith Ta' līl al-Af'āl, and to be able to distinguish between the problems of Kaun and Dīnī. This type of research is qualitative literature research with an intertextual approach from primary and secondary data sources related to the research theme. As for the result, this definition of good and bad does not only affect the principle of aqidah or belief but also widens its influence on the uṣūl al-fiqhdebate which becomes the methodology for taking law on the actions of a mukallafor which is obliged to apply sharia law. In conclusion, the definition of mu'tazilahis that in this case it departs from pure reason, while the definition of asyā'irahdeparts from the limitation of revelation and the rest which is not discussed by revelation is the realm of Allah's will, while Ibn Taimiyyah agrees that good and bad can be seen from both and raises the concept of kauniyyah and syar'iyyah so as not to fall into qadariyyah (denying destiny) and also jabariyyah or mujbirah (stating that all actions are the will of Allah which human not involved at all).